DESCRIPTION OF IMPAIRED VISUAL ACUITY IN ELEMENTARY SCHOOL 5TH DAN 6TH GRADE AT SDN 026 PEKANBARU IN 2014 - Novita Sari; Eka Bebasari; Efhandi Nukman (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTImpaired visual acuity is a very important issue, because 80% of the information obtained from the sense of sight. Snellen and Pinhole test is a technique to determine visual acuity disorders and datasheets/questionnaire is one to assess the characteristics of the respondents sharp vision disorders. Design of the study was deskriftive cross sectional and accidental sampling method done in SDN 026 Pekanbaru a October until November 2014 accordance to the inclusive criteria. Almount of sample are 205 respondents to fill out the data sheet / questionnaire and follow visual acuity examination. The results of this study researchers was respondents impaired visual acuity as much (39.99%), visual disturbances most bilateral visual impairment (71.99%), the highest refractive disorders (92.68%). With sharp vision disorders characteristics the majority of the age group 11-12 years (46.34%), gender more in women (62.19%), a history of using glasses majority (51.2%), family history of heart bespectacled most (73.17%), and nuclear families with glasses more in age <40 years (61.66%).Key words : impared visual acuity, primary school children, refractive desorder